2019
DOI: 10.1200/jco.2019.37.15_suppl.2064
|View full text |Cite
|
Sign up to set email alerts
|

Prospective phase II trial in patients with first relapse of high-grade astrocytoma using TVB-2640 in combination with bevacizumab versus bevacizumab alone.

Abstract: 2064 Background: Recurrent glioblastoma (rGBM) following chemoradiation is associated with a poor prognosis. While bevacizumab is the most common salvage therapy, responses remain brief and without an associated survival benefit. Resistance may involve overexpression of Fatty Acid Synthase (FASN). Our institution is conducting a phase 2 study of bevacizumab with FASN inhibitor TVB-2640 in patients with GBM in first relapse. Methods: This is a prospective, phase 2 study of bevacizumab with TVB-2640 in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…FASN TVB-2640 clinical phase 2 (monotherapy and/or co-treatment) [25,26] Orlistat FDA-approved (as an anti-obesity drug) [27,28] C75 preclinical [29,30] GSK2194069 preclinical [31,32] Fasnall preclinical [33] SCD A939572 preclinical [34,35] MF-438 preclinical [36,37] CAY10566 preclinical [38,39] BZ36 preclinical [40] SREBP1 Fatostatin preclinical [41] FGH10019 preclinical [42] NAFLD, nonalcoholic fatty liver disease; SREBP1, sterol regulatory element-binding protein 1.…”
Section: Drugs Development Stage Referencesmentioning
confidence: 99%
“…FASN TVB-2640 clinical phase 2 (monotherapy and/or co-treatment) [25,26] Orlistat FDA-approved (as an anti-obesity drug) [27,28] C75 preclinical [29,30] GSK2194069 preclinical [31,32] Fasnall preclinical [33] SCD A939572 preclinical [34,35] MF-438 preclinical [36,37] CAY10566 preclinical [38,39] BZ36 preclinical [40] SREBP1 Fatostatin preclinical [41] FGH10019 preclinical [42] NAFLD, nonalcoholic fatty liver disease; SREBP1, sterol regulatory element-binding protein 1.…”
Section: Drugs Development Stage Referencesmentioning
confidence: 99%
“…Moreover, partial results of the phase 2 trial of TVB-2640 in combination with Bevacizumab in patients with the first relapse of high-grade astrocytoma showed that co-treatment is well-tolerated in humans. 118 In 2016, Alwarawrah et al discovered a potent thiophenopyrimidine-based FAS inhibitor with broad antitumor activity against various non-tumorigenic and aggressive tumor-forming breast cancer cell lines. Fasnall (25, Figure 4) with an IC 50 of 3.71 μM for hFAS, can produce a significant change in the global cellular lipid profile.…”
Section: F I G U R Ementioning
confidence: 99%
“…Now, phase 2 of clinical trials of TVB‐2640 (monotherapy and/or co‐treatment) is underway, and includes the treatment of lung, colon, breast, and astrocytoma cancer (NCT03808558, NCT02980029, NCT03179904, and NCT03032484). Moreover, partial results of the phase 2 trial of TVB‐2640 in combination with Bevacizumab in patients with the first relapse of high‐grade astrocytoma showed that co‐treatment is well‐tolerated in humans 118 …”
Section: Lipogenic Enzymes’ Inhibitorsmentioning
confidence: 99%
“…Nowadays, the phase 2 of clinical trials of TVB-2640 (monotherapy and/or cotreatment) is underway, including the treatment of lung, colon, breast, and astrocytoma cancer (NCT03808558, NCT02980029, NCT03179904, and NCT03032484). Moreover, partial results of the phase 2 trial of TVB-2640 in combination with Bevacizumab in patients with the first relapse of high-grade astrocytoma, showed that the co-treatment is well tolerated in humans (117).…”
Section: Acc Function and Descriptionmentioning
confidence: 99%